Retrospective Database Analysis to Explore Patterns and Economic Burden of Switchback to Brand After Generic or Authorized Generic Utilization - Alderfer J; Aggarwal J; Gilchrist K; Alvir JMJ; Cook J; Park SH; Stephens JM (Dove Medical Press, 2022)
Justine Alderfer,1 Jyoti Aggarwal,2 Kim Gilchrist,1 Jose Maria Jimenez Alvir,3 Joseph Cook,4 Sang Hee Park,5 Jennifer M Stephens5 1Medical Affairs, Pfizer Inc., Collegeville, PA, USA; 2Evidence & Access, OPEN Health, Newton, MA, USA; 3Global Product Development, Pfizer Inc., New York, NY, USA; 4Clinical Development and Medical Affairs, Viatris, Canonsburg, PA, USA; 5Evidence & Access, OPEN Health, Bethesda, MD, USACorrespondence: Justine Alderfer, US Medical Affairs, Pfizer, 500 Arcola Rd., Collegeville, PA, 19426, USA, Tel +1 484-865-3105, Email Justine.Alderfer@pfizer.comBackground: Despite demonstration of bioequivalence of generics to brands and the potential for reduced costs, some patients switch back from a generic to the brand. A prior retrospective analysis suggested that this switchback rate may be lower among patients that had initially switched to authorized generics (AG), often both produced and marketed by the brand company, compared to those initially switched to another generic.Objective: Explore switching patterns of brands, AGs, and generics, switchback rates, and the potential impact of switchbacks on healthcare costs.Methods: An analysis of the Pharmetrics Plus™ database (2007- 2019), a United States (US) payer administrative database, was conducted to examine the use of Upjohn medications available as AGs across multiple therapeutic areas. Patients initiating treatment with brand medication in the 6 months prior to generic market entry were identified and switch rates to generics and AGs, as well as switchback rates, were evaluated. Costs were descriptively compared between patients who switched back to brand and those who remained on any generic.Results: Across 14 brand medications, more than half of the patients initiating treatment with the brand medication were switched to a generic. Generally, switching to AG, which ranged from 0.5 to 39.6%, was lower than switching to non-AG generics (16.7- 79.9%). The comparison of switchback rates from AGs to brand and non-AGs to brand showed similar results (AG:1.3- 7.5%; non-AG:1.4- 12.9%); however, the most substantial differences were observed where non-AG switchbacks were higher. Patients that switched back to brand remained on AG or generic for an average of 1- 3 months (32- 88 days). The analysis showed a tendency towards increased medical costs in the period immediately preceding switchback for all medications except sildenafil in both indications (erectile dysfunction and pulmonary arterial hypertension). For the remaining medications, medical costs ranged from $63 to $1544 higher for the switchback population. Pharmacy costs similarly tended to be higher for patients who had a switchback, with the exception of sildenafil for pulmonary arterial hypertension and sirolimus.Conclusion: Patients receiving a brand medication are likely to be switched to a generic upon market availability. Some patients switch back to the brand medication, usually within 1- 3 months; this may be associated with increased medical costs. Additional research is needed to understand switching, its potential disruption to patients, and the role of brands, generics, and AGs.Keywords: authorized generic, Generic, medication switching, costs